2012
DOI: 10.1016/s1001-0742(11)60746-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of source water contamination by estrogenic disrupting compounds in China

Abstract: Detection of estrogenic disrupting compounds (EDCs) in drinking waters around China has led to rising concerns about health risks associated with these compounds. There is, however, a paucity of studies on the occurrence and identification of the main compounds responsible for this pollution in the source waters. To fill this void, we screened estrogenic activities of 23 source water samples from six main river systems in China, using a recombinant two-hybrid yeast assay. All sample extracts induced significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 49 publications
4
36
0
2
Order By: Relevance
“…The measured EEQ in surface water of this study (Table 1; Fig. 2) are in a similar range to a previous report on the Guangzhou section of the Pearl River system ), but much higher than the EEQ for six major source waters (0.08-2.40 ng E2/L) (Jiang et al 2012), and much lower than the highest EEQ (4610 ng E2/L) of the rivers in the United States (Alvarez et al 2013). The present study also showed much higher EEQ in the Shima River and Danshui River than Xizhijiang River and Dongjiang River, since the former two rivers receive large volumes of treated and untreated wastewaters from Shenzhen, Dongguan and Huizhou cities (Chen et al 2014a, b).…”
Section: Results and Discussion Eeq Measured By Yes Bioassaysupporting
confidence: 89%
“…The measured EEQ in surface water of this study (Table 1; Fig. 2) are in a similar range to a previous report on the Guangzhou section of the Pearl River system ), but much higher than the EEQ for six major source waters (0.08-2.40 ng E2/L) (Jiang et al 2012), and much lower than the highest EEQ (4610 ng E2/L) of the rivers in the United States (Alvarez et al 2013). The present study also showed much higher EEQ in the Shima River and Danshui River than Xizhijiang River and Dongjiang River, since the former two rivers receive large volumes of treated and untreated wastewaters from Shenzhen, Dongguan and Huizhou cities (Chen et al 2014a, b).…”
Section: Results and Discussion Eeq Measured By Yes Bioassaysupporting
confidence: 89%
“…Exogenous steroid chemicals are widely detected in a number of water systems, ranging from several to hundreds ng/L (Backe et al, 2011;Chang et al, 2011;Jiang et al, 2012;Zhou et al, 2012). These compounds produce detrimental biological effects even at low ng/L levels (Filby et al, 2007;Leet et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogenic chemicals, such as estrone (E1), 17b-estradiol (E2), estriol (E3) and 17a-ethinylestradiol (EE2) and androgenic chemicals, such as methyltestosterone, testosterone, and androstenedione have been detected in a number of water systems at concentration levels between 1 and 100 ng/L (Backe et al, 2011;Chang et al, 2011;Jiang et al, 2012;Zhou et al, 2012). Even at low ng/L, these exogenous steroid chemicals have the potential to produce detrimental biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…In risk assessment, by comparing EEQs obtained from both analytical determination and bioassay, the major and minor contributors of a complex sample could be identified. When this was applied to environmental waters, some work reported that the predicted overall EEQs were similar to observed ones (Beck et al, 2006;Jiang et al, 2012;Liscio et al, 2009), but some found that the predictions were higher or lower (Cargouët et al, 2004;Furuichi et al, 2004). These contradictory conclusions may result from the contribution of non-targets chemicals such as unknown estrogen agonist, antagonist and humics, or the multiple involved modes of action (MoAs) and the resulting interaction of mixture components (Villeneuve et al, 2000).…”
Section: Introductionmentioning
confidence: 98%